(Re)Inserting the Subjective “I”: Globalization, neoliberalism & student agency in post-secondary education - DesRoches, Sarah (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique de l’Université de Montréal, 2011)
In an increasingly globalized world, post-secondary education is being reduced to instrumental and economic ends; a significant effect of this is that student agency is undermined. Students are incited to perform neo-liberal values that subvert their willingness (and potentially their ability) to think of their post-secondary experience as anything other than professional training. Neo-liberal values do inhibit individuality and agency within a post-secondary context; however, from a Foucaultian perspective, the dominant discourse can never squelch the possibility of alternative discourses from emerging, thereby unhinging the seemingly cemented reality described above. In the first section of this paper, I will provide a theoretical overview of globalization, its relationship to neo-liberalism and how these have impacted post-secondary education. This overview will enable me to consider a very specific example of how neo-liberal ideology is being manifested in post-secondary classrooms: namely, the reluctance of pre-service teachers to use the first person singular pronoun in their research papers.